Effect of A-site substitution by Ca or Sr on the structure and electrochemical performance of LaMnO3 perovskite. (1st February 2020) - Ma, Pian Pian; Lu, Qiu Ling; Lei, Na; Liu, Yong Kun; Yu, Bo; Dai, Jian Ming; Li, Shu Hong; Jiang, Guo Hua
Abstract: The effect of A-site substitution by Ca or Sr on the crystal structure and electrochemical performance of LaMnO3 (LMO) perovskite have been investigated. La0.85 Ca0.15 MnO3 (LCM) keeps the same orthorhombic structure with the parent LMO composition, while La0·85 Sr0·15 MnO3 (LSM) transforms to rhombohedral structure. The A-site substituted compositions with more oxygen vacancies are more beneficial to the oxygen intercalation than the parent LMO sample according to the modified anion-intercalation mechanism, and the electrochemical performance is significantly optimized. LCM and LSM electrodes exhibit a specific capacitance of 140.5 mF cm −2 and 129.0 mF cm −2  at 0.5 mA cm −2 in an aqueous electrolyte, respectively, which are four times larger than that of LMO. LCM electrode yields the highest capacitance behavior because of the finer morphology, lower ion diffusion resistance, higher concentration of oxygen vacancy and fuller utilization of the perovskite bulk structure. In addition, LCM//LCM symmetric supercapacitor exhibits an energy density of 29.7 μWh . cm −2  at a powder density of 500 μW cm −2 . Our work indicates that A-site substituted compositions by Ca or Sr exhibit great potential in the supercapacitor applications, and further optimization is expected. Highlights: LCM keeps orthorhombic structure, while LSM transforms to rhombohedral structure. A modified oxygen-intercalation mechanism for LCM and LSM is provided. After substituted by Ca or Sr, the capacitances reach more than quadrupled. The reasons for highest capacitance behavior of LCM are overall analyzed.